Anti–tumor necrosis factor alpha therapy (adalimumab) in Rasmussen's encephalitis: An open pilot study. (22nd April 2016) - Lagarde, Stanislas; Villeneuve, Nathalie; Trébuchon, Agnès; Kaphan, Elsa; Lepine, Anne; McGonigal, Aileen; Roubertie, Agathe; Barthez, Marie‐Anne J.; Trommsdorff, Valérie; Lefranc, Jérémie; Wehbi, Samer; des Portes, Vincent; et al.
Summary: Objective: Rasmussen's encephalitis (RE) is a severe chronic inflammatory brain disease affecting one cerebral hemisphere and leading to drug‐resistant epilepsy, progressive neurologic deficit, and unilateral brain atrophy. Hemispherotomy remains the gold standard treatment but causes permanent functional impairment. No standardized medical treatment protocol currently exists for patients prior to indication of hemispherotomy, although some immunotherapies have shown partial efficacy with functional preservation but poor antiseizure effect. Some studies suggest a role for tumor necrosis factor alpha (TNF‐α) in RE pathophysiology. Methods: We report an open‐label study evaluating the efficacy and the safety of anti‐TNF‐α therapy (adalimumab) in 11 patients with RE. The primary outcome criterion was the decrease of seizure frequency. The secondary outcome criteria were neurologic and cognitive outcomes and existence of side effects. Results: Adalimumab was introduced with a median delay of 31 months after seizure onset (range 1 month to 16 years), and follow‐up was for a median period of 18 months (range 9–54 months). There was a significant seizure frequency decrease after adalimumab administration (from a median of 360 to a median of 32 seizures per quarter, p ≤ 0.01). Statistical analysis showed that adalimumab had a significant intrinsic effect (p < 0.005) independent from disease fluctuations. Five patients (45%) were found to have sustained improvement over consecutive quarters in seizure frequency (decrease of 50%) on adalimumab. Three of these five patients also had no further neurocognitive deterioration. Adalimumab was well tolerated. Significance: Our study reports efficacy of adalimumab in terms of seizure frequency control. In addition, stabilization of functional decline occurred in three patients. This efficacy might be particularly relevant for atypical slowly progressive forms of RE, in which hemispherotomy is not clearly indicated. Due to our study limitations, further studies are mandatory to confirm these preliminary results.